'Bad for the Health of the Body, Worse for the Health of the Mind': Female Responses to Imprisonment in England, 1853–1869. (18th January 2020) - Bennett, Rachel
Abstract: Upon committal to one of the newly established female convict prisons in the mid-nineteenth century, women entered a system intended to regulate them in body and in mind for the ends of reform. This article interrogates how women's health needs were identified and contested by the prison officials and doctors tasked with their custody and care. It highlights the importance of broader temporal gender beliefs in dictating their treatment in this carceral space and explores how the women themselves exercised agency over the terms of their imprisonment. In addition, it reveals the previously underexplored transference of women between the institutions that made up the female convict estate that was prompted by concerns about the impact of a rigorous prison system on their physical and mental health.